Evaluasi Rekayasa Ekstraksi Biji, Minyak, dan Limbah Habbatussauda (Nigella sativa) terhadap Komponen Bioaktif dan Kemampuan Penghambatan Bakteri: Evaluation of the Extraction Process of Seeds, Oil, and Waste of Black Seed (Nigella sativa) on Bioactive Compound and Bacterial Inhibition Ability - Barkah, Nisa Nurmilati; Wiryawan, I Komang Gede; Retnani, Yuli; Wibawan, I Wayan Teguh; Wina, Elizabeth (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2025)
The content of active compounds in natural materials is generally low and highly variable, thus requiring efficient and selective extraction methods. This study aims to evaluate a stepwise extraction process applied to the seeds, oil, and by-products of Nigella sativa (black cumin) to obtain thymoquinone (TQ) and other phytochemicals. The study consisted of four main stages: (1) extraction of HS oil using the cold press method, (2) stepwise extraction using 70% ethanol as solvent, (3) analysis of TQ content and phytochemical compounds in the extracts, and (4) evaluation of the antibacterial activity of habbatussauda oil extracts against pathogenic and non-pathogenic bacteria. Results showed that the cold press method yielded 34.46% oil. Stepwise extraction using 70% ethanol resulted in significant differences (p<0.05) in both yield and TQ content among the seed, oil, and by-product extracts. Among all samples, the ethanol extract from habbatussauda oil exhibited the highest yield and TQ concentration. Furthermore, at a concentration of 100 μg mL⁻¹, this extract inhibited the growth of pathogenic bacteria such as Salmonella typhimurium and Escherichia coli, without affecting non-pathogenic strains like Lactobacillus spp. and Bifidobacteria spp. In conclusion, stepwise extraction using 70% ethanol proved effective in enhancing TQ recovery and demonstrated potential as a phytobiotic agent with selective antibacterial activity against pathogenic bacteria. Key words: black seed, phytobiotic, phytochemicals, stepwise extraction, thymoquinone